Aerodynamic response of a blade cascade to torsional excitation of one blade at subsonic and transonic velocities - David Šimurda; Jiří Fürst; Josef Musil; Petr Šidlof; Jan Lepicovsky (Propulsion and Power Research)
The trend of increasing the power-to-weight ratios of aircraft turbofan engines and efficiency of steam turbines leads to designs with long and slender blades often operating at transonic flow conditions. Such blades are prone to undesirable and possibly destructive vibrations caused by engine-order excitation or induced by flow itself. To shed more light on this problem and to extend the existing knowledge, this paper presents experimental and numerical study on torsional mode vibration of one blade in a linear blade cascade of flat profiles. In this study, dynamic loading and pressure distributions were investigated at subsonic, supercritical and transonic flow regimes while the blade was kinematically excited by a motor and shaft mechanism at reduced frequencies up to k = 0.47. Dynamic flow structure development was documented and analyzed based on numerical simulations. Furthermore, dependence of energy transfer over an oscillation cycle on frequency and exit Mach number was investigated. Results revealed significant hysteresis in the flow field configuration particularly at supercritical and transonic cases. Hysteresis is manifested namely by different development of supersonic regions when the oscillating blade passes through the zero deflection during upstroke and downstroke. Resulting aerodynamic moment is non-harmonic and there is an increasing phase lag with respect to the blade deflection when oscillation frequency increases. In majority of investigated regimes, hysteresis resulted in aerodynamic damping of the blade oscillation.